2022
DOI: 10.4081/ejh.2022.3426
|View full text |Cite
|
Sign up to set email alerts
|

MALAT1 regulates hypertrophy of cardiomyocytes by modulating the miR-181a/HMGB2 pathway

Abstract: Noncoding RNAs are important for regulation of cardiac hypertrophy. The function of MALAT1 (a long noncoding mRNA), miR-181a, and HMGB2; their contribution to cardiac hypertrophy; and the regulatory relationship between them during this process remain unknown. In the present study, we treated primary cardiomyocytes with angiotensin II (Ang II) to mimic cardiac hypertrophy. MALAT1 expression was significantly downregulated in Ang II-treated cardiomyocytes compared with control cardiomyocytes. Ang II-induced car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Xu et al have recently identified many genes that are differently expressed in cardiomyocytes and vascular endothelial cells of heart patients infected with COVID-19, including MALAT1, CD36, LARGE1, RYR2, PLCG2 (in cardiomyocytes), MALAT1, ID1, ID3, MT-CO1 and EGFL7 (in vascular endothelial cells) (87) . These genes regulate many vital functions in these cardiac cells (88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103) . The discovery of these novel contributors of COVID-19 mediated cardiac pathophysiology may help identify novel therapeutic targets.…”
Section: Long-term Cardiovascular Results With Covid-19 Pearlsmentioning
confidence: 99%
“…Xu et al have recently identified many genes that are differently expressed in cardiomyocytes and vascular endothelial cells of heart patients infected with COVID-19, including MALAT1, CD36, LARGE1, RYR2, PLCG2 (in cardiomyocytes), MALAT1, ID1, ID3, MT-CO1 and EGFL7 (in vascular endothelial cells) (87) . These genes regulate many vital functions in these cardiac cells (88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103) . The discovery of these novel contributors of COVID-19 mediated cardiac pathophysiology may help identify novel therapeutic targets.…”
Section: Long-term Cardiovascular Results With Covid-19 Pearlsmentioning
confidence: 99%
“…Increased MALAT1 expression enhances cardiomyocyte apoptosis [50,82,83], and MALAT1 is highly expressed in patients with acute myocardial infarction [84,85]. However, the low expression of MALAT1 may promote myocardial hypertrophy [86].…”
Section: Qualitative Features In Cardiomyocytesmentioning
confidence: 99%
“…Low MALAT1 expression in cardiomyocytes can cause damage to the hearts of COVID-19 patients. Chen et al [86] found that MALAT1 knockout exacerbates angiotensin II-induced cardiac hypertrophy, suggesting that patients with COVID-19 are susceptible to myocardial hypertrophy. As for the second parameter, TTN (ENSG00000155657), which was shown downregulated in this rule, was used in distinguishing patients with COVID-19.…”
Section: Quantitative Rules In Cardiomyocytesmentioning
confidence: 99%
“…Similarly, MALAT1 acts as a sponge to inhibit miR-181a, which is up regulated in angiotensin II-treated cardiomyocytes. Decreased expression of MALAT1 promotes miR-181a-induced cardiac hypertrophy by decreasing the expression of HMGB2 (33). By sequestering miRNAs, MALAT1 The roles of MALAT1 in bone and cartilage diseases.…”
Section: The Biological Functions Of Malat1 As a Competing Endogenous...mentioning
confidence: 99%
“…Similarly, MALAT1 acts as a sponge to inhibit miR-181a, which is up regulated in angiotensin II-treated cardiomyocytes. Decreased expression of MALAT1 promotes miR-181a-induced cardiac hypertrophy by decreasing the expression of HMGB2 ( 33 ). By sequestering miRNAs, MALAT1 may directly/indirectly regulate the pathophysiological processes of many diseases, providing a potential target for clinically therapeutic management ( Figure 1 ).…”
Section: The Biological Activities Of Malat1mentioning
confidence: 99%